2011
DOI: 10.3382/japr.2010-00190
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tropical environmental conditions on the stress and immune responses of commercial broilers, Thai indigenous chickens, and crossbred chickens

Abstract: Heat stress is a life-threatening factor in commercial broilers raised in the tropics (e.g., Thailand) without temperature-controlled housing facilities. However, these temperature-controlled facilities are hardly affordable by small-scale farmers. To avoid such limitations, a Thai indigenous crossbred line (C line), selected as a candidate meat-type chicken to survive in the tropical environment, was examined for its capacity to tolerate the tropical climate and for its immune functions. Comparisons, in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…This magnitude of mortality is not surprising, since meat broiler chickens are vulnerable to various environmental pressures, including natural disasters [28], infectious diseases [29], and temperature change [30]. All of these drivers of avian mortality are likely intensified within tropical environments [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…This magnitude of mortality is not surprising, since meat broiler chickens are vulnerable to various environmental pressures, including natural disasters [28], infectious diseases [29], and temperature change [30]. All of these drivers of avian mortality are likely intensified within tropical environments [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Tirawattanawanich et al . [ 46 ] revealed that Thai indigenous crossbred chickens had a better tolerance to heat stress than modern broiler chickens. Due to the latter study and the fact that the experiment was conducted during the rainy season (average temperature during the day was 30°C±2°C), the vitamins and minerals supplementation seemed to produce minimal effect as the Indonesian indigenous crossbred chickens less suffered from heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Stresses, such as heat stress, or food and water restriction, is known to be detrimental to the chicken's immune function, altering tissue invasion of intestinal bacteria [ 24 , 25 ]. However, different types or lines of chickens show variation in both the effect of heat stress on their immune response [ 26 ] and their ability to regulate the immune response to Campylobacter [ 27 ]. The links between management system, chicken welfare, stress and the biology of Campylobacter infections remain poorly understood, but have raised concerns about how farming systems may impact on public health risk [ 28 – 30 ].…”
Section: Introductionmentioning
confidence: 99%